Situational analysis in the study of urban everyday life - Pawlik, Jacek Jan (A mosaic city: The culture-oriented description, 2023)
This paper presents the application of the situational approach to the study of urban communities. This approach is particularly useful for the study of everyday life and is closely linked to network analysis. After presenting the theoretical assumptions of the approach, the author analyses three cases of situations from his field research conducted in Lomé, the capital of Togo. It appears that situational analysis combined with structural analysis provides an adequate picture of urban life.